2022
DOI: 10.1039/d1lc01053k
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic harvesting of breast cancer tumor spheroid-derived extracellular vesicles from immobilized microgels for single-vesicle analysis

Abstract: Investigating cellular and vesicular heterogeneity in breast cancer remains a challenge, which encourages the development of controllable in vitro systems that mimic the tumor microenvironment. Although three-dimensional cell culture better...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 104 publications
(120 reference statements)
1
9
0
Order By: Relevance
“…Sung et al [ 101 ] described an automated and highly sensitive integrated microfluidic platform featuring a sample treatment to microRNA biomarker quantification from 20 µL plasma in ovarian cancer. Rima et al [ 102 ] developed a novel microfluidic system to collect EVs generated from breast cancer tumor spheroids, thereby enabling analysis at the single-vesicle level. Niu et al [ 103 ] designed a fluid nanoporous microinterface (FluidporeFace) in a microfluidic chip to enhance the isolation efficiency of EVs derived from the tumor.…”
Section: Methods Of Ev Isolationmentioning
confidence: 99%
“…Sung et al [ 101 ] described an automated and highly sensitive integrated microfluidic platform featuring a sample treatment to microRNA biomarker quantification from 20 µL plasma in ovarian cancer. Rima et al [ 102 ] developed a novel microfluidic system to collect EVs generated from breast cancer tumor spheroids, thereby enabling analysis at the single-vesicle level. Niu et al [ 103 ] designed a fluid nanoporous microinterface (FluidporeFace) in a microfluidic chip to enhance the isolation efficiency of EVs derived from the tumor.…”
Section: Methods Of Ev Isolationmentioning
confidence: 99%
“…Relative and total fluorescent intensities of the sample were obtained from custom-built algorithms that were previously reported. (31, 37)…”
Section: Methodsmentioning
confidence: 99%
“…Scatter plots were generated with the mean intensity and size of the single spots detected by TIRFM. Relative and total fluorescent intensities of the sample were obtained from custom-built algorithms that were previously reported (31, 37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the heterogeneity of EVs, the detection of single EVs is also significant. [ 87 ] Nguyen et al designed a highly sensitive immunogold‐based biochip, as shown in Figure 6 . First, a thin gold coating was deposited on glass coverslips by titanium, followed by coating with PEG, after which AuSERPs were assembled by attaching functionalized glass coverslips to silicone gaskets with 64 chambers, and then the treated glass surfaces with a mixture of streptavidin‐conjugated AuNP followed by biotinylated antibody mixture to capture specific EV subpopulations was functionalized.…”
Section: Membrane Fusion‐based In Situ Detectionmentioning
confidence: 99%